Fair Competition as the Basic Problem of Market Economy - Taliashvili, Alexandre (Advances in Social Sciences Research Journal, 2020)
In the Economy, both the level and forms of competition significantly determine market structure, investment opportunities,trade balance of the country as well as the degree of fairness and transparency in the process of distribution of public wealth and income. The existing injustice in both economy and business has revealed new themes and directions that are exactly in line with the times. In EU countries the legitimate questions about justice are the following: Why did the economic development create a huge level of property inequality under the conditions of globalization,in economically successful countries? Why do transnational corporations violate the conditions of fair competition? How pervasive is the problem of inequality in our world? and How inequality is reflected between the objective perception of reality and its subjective understanding? Does the competition have the natural ability to regulate market relations without causing a sense ofinjustice and inequality? Economists, lawyers, philosophers and political scientists try to find a logical answer to these questions. We think that the fair competition is a fundamental problem of the market economy. It must ensure the sustainable development of society, reduce the recurrence of economic crises and limit both the process of business expansion and total formation of monopolies.The problem of fair competition requires special research and we have paid great attention to it in our paper.